Genossensor eletroquímico contendo nanopartículas de ouro Para detecção sensível de sars-cov-2 - Reis, Marco Túlio de Freitas (Universidade Federal de São Carlos, 2022)
Since the emergence of the new coronavirus (SARS-CoV-2), more than 495 million people have been affected by this disease, leading to an estimated 6.17 million deaths. In this context, the World Health Organization (WHO) described social distancing and isolation of infected individuals as some of the main methods to contain the spread of the virus. Therefore, early diagnosis of COVID-19 is extremely important to fast treat and isolate infected individuals, preventing the advancement of the disease and more serious health conditions. Currently, the gold standard for diagnosing the disease is qPCR. Despite its high sensitivity and low detection limits, it demands advanced laboratory infrastructure, skilled labor, sample transport and is expensive. In this sense, the development of tools for the diagnosis of COVID-19 in a simple, fast, low-cost and in situ way is of great interest. The present study shows the development of a disposable and portable electrochemical genosensor capable of detecting the cDNA of SARS-CoV-2. For this, carbon electrodes were produced using the screen printing technique, and gold nanoparticles were deposited on its surface to increase sensitivity and facilitate the immobilization of biomolecules. cDNA sequences specific of SARS-CoV-2 were immobilized on the electrode surface on self-assembled monolayers using mercaptoacetic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, and the presence of the analyte was evaluated by electrochemical impedance spectroscopy (EIS). After optimizing the parameters for biosensor assembly, it was possible to build a calibration curve for target DNA concentrations between 0.2 μmol L -1 and 10.0 μmol L -1 , showing the device's potential for detecting the desired sequence. Next steps include performing additional optimizations in the biosensor assembly protocol, mainly aiming at increasing reproducibility and decreasing the detection limit of the device. It is expected that, in the future, the developed biosensor will prove to be a portable, accurate, fast and low-cost tool for the diagnosis of SARS-CoV-2.
Electrochemical genosensor containing gold nanoparticles for sensitive detection of sars-cov-2
Keywords: Biossensor; Eletroquímica; SARS-CoV-2; COVID-19; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA